Effect of Irrigation Regime and Fertilization on Recovery of Dicamba Injured Soybean - Wesley France; Jason Norsworthy; Trent Roberts; Jeremy Ross; Tom Barber; Edward Gbur (International Journal of Agronomy)
With the release of the dicamba-resistant crop technology and subsequent increase in dicamba off-target movement to non-dicamba-resistant crops, discovering means of mitigating yield loss through studying dicamba injury to soybean and interactions with factors such as irrigation regime and fertilization would prove beneficial. Field experiments were conducted in 2019 in Fayetteville and Colt, Arkansas, to evaluate the effect of irrigation regime to non-dicamba-resistant soybean that was injured by dicamba at a low dose at multiple timings. Another experiment was conducted in Fayetteville in 2019 and 2020 evaluating the impact of nitrogen (N) and potassium (K) fertilization on soybean recovery following injury by dicamba at multiple reproductive stages. Visible injury in both experiments was affected by application timing. Soybean yield components were impacted by dicamba applications within the irrigation regime experiment, and yields were decreased by dicamba applications; however, soybean yield was higher from branches than from the mainstem in dicamba-treated compared to nontreated plants. In the fertilization experiment, soybean treated with a low dose of dicamba that received N fertilization tended to have reduced biomass compared to treatments receiving no fertilizer or K alone, with greatest biomass reduction tending to occur among treatments receiving both N and K. Total grain yield was not affected by either irrigation regime or fertilization. While an increase in yield due to neither irrigation nor fertilization was observed, these results may help improve understanding of the effect of low-dose dicamba on soybean and aid producers making management decisions.